Lack of association between methylenetetrahydrofolate reductase C677T polymorphism, HPV infection and cervical intraepithelial neoplasia in Brazilian women - Nayara Nascimento Toledo Silva; Adriano de Paula Sabino; Alexandre Tafuri; Angélica Alves Lima (BMC, 2019)
Abstract Background Cervical cancer has high prevalence and mortality rates in worldwide female population. Persistent infection by high-risk Human Papillomavirus (hr-HPV) is the main cause of this cancer. However, many environmental, genetical, and epigenetical cofactors can modulate viral infection and cervical carcinogenesis. Methylenetetrahydrofolate reductase (MTHFR) C677T polymorphism is a genetic factor that has been associated with many pathologies, including cancer. Nevertheless, studies with cervical cancer presented controversial results, and varied according to ethnicity. Thus, the aim of this study was to determine association between MTHFR C677T polymorphism, Human Papillomavirus (HPV) infection and cervical cancer. Methods A case-control study was performed with 150 histological cervical samples. Case group were divided in Cervical Intraepithelial Neoplasia (CIN) grade I (n = 30), CIN II (n = 30), CIN III (n = 30), and Squamous Cervical Carcinoma (SCC) (n = 30). Control group was composed by 30 samples without lesion, presenting cervicitis. HPV detection was performed by conventional Polymerase Chain Reaction (PCR) with SPF primers set, and by real-time PCR specific for HPV 16 and hr-HPV. MTHFR C677T polymorphism was analyzed by PCR followed by Restriction Fragment Length Polymorphism (RFLP). Results Frequency of MTHFR CC genotype was 72.7% (n = 109), CT 23.3% (n = 35) and TT 4.0% (n = 6). Polymorphic T allele frequency was 15.7%. No statistically significant association was observed between MTHFR C677T polymorphism and presence of pre-neoplastic or neoplastic cervical lesions. Similar frequencies of T allele was observed in control (23.3%) and cases (13.3%) groups (p = 0.174). In addition, there was no statistically significant association between MTHFR C677T polymorphism and viral infection, even considering hr-HPV or HPV 16 positivity. Conclusion MTHFR C677T polymorphism was not associated with cervical cancer and HPV infection.